ANALYSIS OF THE LAYOUT OF THE COMPANY'S FACILITIES ON WORK PRODUCTIVITY WITH THE 5S PRINCIPLE AND THE ACTIVITY RELATIONSHIP CHART IN CV. TATA JAYA SCREEN PRINTING - Putra, Nur Rizky Maulana; Kirono, Indro (Dynamic Management Journal, 2025)
CV. Tata Jaya Sablon is a textile company that produces various types of clothing, including t-shirts, shirts, polos, jackets, and more. This company employs several workers who sew and carry out various phases of the production process every day. Based on the results of field observations, it is known that the production process has a fairly long process flow with limited production space. This study aims to provide an ideal production facility layout design in order to create an effective and efficient work environment. This study was conducted using the 5S methodology (seiri, seiton, seiso, seiketsu, shitsuke) to optimize space utilization and create a proposed layout based on the ARC diagram. The results of this study show that the organization's 5S implementation score reached 75%, so it was given the predicate "Quite Good". However, seiri and seiton have the lowest score, so it is necessary to procure a special area for unneeded goods and create a special area to tidy up goods needed for the production process. The ARC results show that the proposed layout has succeeded in increasing the efficiency of the moment of movement or distance of movement by 29.21%.